Indoor localization algorithm based on RFID technology for smart park - Wenzhao WU; Xiao WANG; Kunpeng ZHAO; Yafeng WEN (Dianxin kexue)
To meet the various requirements of full range management of vast device in buildings of smart park，an indoor localization algorithm about information fusion of multi readers was proposed.Based on device management in RFID system，using the wireless sensing characteristics between the reader and the tag，and combining with the reference tag concept，an indoor localization algorithm based on RFID was proposed.The algorithm had the characteristic of high position accuracy，low complexity and low cost.This algorithm could realize the localization of device tag in smart buildings，and realize management to a large number of device in buildings of smart park more efficiently and intelligently.